Irradiation embrittlement of reactor pressure vessels (RPVs) in nuclear power plants - Soneda, Naoki (Woodhead Publishing in energy, 2015)
Reactor Pressure Vessels (RPVs) contain the fuel and therefore the reaction at the heart of nuclear power plants. They are a life-determining structural component: if they suffer serious damage, the continued operation of the plant is in jeopardy. This book critically reviews irradiation embrittlement, the main degradation mechanism affecting RPV steels, and mitigation routes for managing the RPV lifetime. Part I reviews RPV design and fabrication in different countries, with an emphasis on the materials required, their important properties, and manufacturing technologies. Part II then con.